Peningkatan Jangkauan Pemasaran di Era Digital Menggunakan Akun Shopee pada Savira Frozen Food Home Made: Expanding Marketing Reach in the Digital Era Using a Shopee Account at Savira Frozen Food Home Made - Syamsuri, Syamsuri; Rumasukun, Muhammad Alfan; Rahayu, Amin Fonda Astiti Rob; Kamaluddin, Imam; Jamal, Mulyono (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Savira Frozen Food Home Made is a micro-enterprise producing homemade frozen foods made from chicken. Despite offering high-quality products and receiving positive customer reviews, the business continues to face challenges in expanding its marketing reach. This is primarily because Savira Frozen Food Home Made relies solely on WhatsApp to offer and promote its products. As a result, it can only reach customers who already have and have saved the business's contact number. Sales are still carried out directly from the home as well. This community engagement initiative aims to broaden the marketing reach of Savira Frozen Food Home Made through the Shopee e-commerce platform. By utilising this digital platform, business opportunities and potential increases in income through expanded market reach are expected to grow significantly. It may also enhance the competitiveness of micro-enterprise products in the business world. The implementation methods include training and mentoring in creating a Shopee account, developing digital marketing strategies, optimising Shopee Ads features, and managing customer service and delivery. The mentoring results show an increase in marketing reach, with the products reaching 6 out of the 21 sub-districts in Ponorogo. These results demonstrate that using digital platforms can effectively expand the market of micro-enterprises and increase the competitiveness of their products more broadly.